The impact of compost and expanded perlite on soil physical properties and water productivity under different irrigation practices - Shahadha, Saadi Sattar; Al-Dharob, Mohammed; Al-Jubouri, Mohammed; Salih, Riyadh (Journal of Aridland Agriculture, 2023)
Finding an appropriate field management strategy for improving crop and water production becomes an imperious necessity because of the irrigation water deficiency in most of the agricultural fields in Iraq. Studying the response of soil properties to the applied soil amendments represents one of the critical parameters in agricultural field management for improving crop production and water use efficiency of Iraqi strategic crops. The effect of soil amendments (compost = 7.5 t/ha and perlite/0.1% Polyvinyl alcohol = 0.25 t/ha) on the water use efficiency and crop production under three levels of water depletion (30, 50, and 70%) of the available soil water was examined for wheat and barley crops. The study was applied under the sprinkler irrigation system. The experimental design was RCBD within 6 treatments and 3 replications for each wheat and barley. The results show that the soil amendments of expanded perlite and compost exhibit an improvement in the soil properties of soil bulk density and soil water content. Soil amendments, especially, the expanded perlite improved the crop yield and water use efficiency under all irrigation levels. The effect of expanded perlite shows the maximum effect on barley production under the 50% irrigation level with 3500 kg/ha. The irrigation level of 70% could be a worth-able management strategy if it is associated with the soil amendments of compost and expanded perlite. As a result, the effectiveness of expanded perlite increased with the increase in the drought of Iraqi soil.